A randomized trial involving a multifunctional diet reveals systematic lipid remodeling and improvements in cardiometabolic risk factors in middle aged to aged adults - Arroyo, Claudia Balderas; Ocariz, Maider Greño; Rogova, Oksana; Al-Majdoub, Mahmoud; Björck, Inger; Tovar, Juscelino; Spégel, Peter (Frontiers in Nutrition, 2023)
A multifunctional diet (MFD) combining foods and ingredients with proven functional properties, such as fatty fish and fibre-rich foods, among others, was developed and shown to markedly reduce cardiometabolic risk-associated factors. Here, we aim at examining metabolic physiological changes associated with these improvements. Adult overweight individuals without other risk factors were enrolled in an 8-week randomized controlled intervention (NCT02148653, https://clinicaltrials.gov/ct2/show/NCT02148653?term=NCT02148653&draw=2&rank=1) following a parallel design, with one group (n=23) following MFD and one group (n=24) adhering to a control diet (CD) diet that followed the caloric formula (E%) advised by the Nordic Nutritional Recommendations. Plasma metabolite and lipids were profiled by gas chromatography and ultrahigh performance liquid chromatography / mass spectrometry. Weight loss was similar between groups. The MFD and CD resulted in altered levels of 137 and 78 metabolites, respectively. Out of these, 83 were uniquely altered by the MFD and only 24 by the CD. The MFD-elicited alterations in lipid levels depended on carbon number and degree of unsaturation. In conclusion, an MFD elicits weight loss-independent systematic lipid remodelling, promoting increased circulating levels of long and highly unsaturated lipids.